ANALISYS RESIKO POSTURE PADA DESAIN KURSI PENGEMUDI BAJAK SAWAH - Rossi S Wahyuni; Mei Raharja; Yuyun Yuniar Rohmatin; Adil Areza (Asosiasi Dosen Muda Indonesia, 2024)
Farmers use tractors to shorten land processing time so that it is completed quickly and the results of land are better. Farmers risk of posture injury when operating a tractor. The RULA (Rapid Upper Limb Assessment) is one methods used to investigate the risk of abnormalities will be experienced in carrying work activities. This research is to analyze the risk of farmers' posture when using paddy plow tractor seat. The risk of farmers' posture when driving a rice plow using results seat on paddy field plow is dominantly green, which means the posture is acceptable, where the final score value in the RULA analysis output results is 2, which means the worker works with a posture that has no risk injury.